TO STUDY THE EFFICACY OF RASONADIGHANAVATI IN THE MANAGEMENT OF AMAVATA - Bansode Janaki Sudhakar; C.S.Majgaonkar (International Journal of Applied Ayurved Research, 2017)
Amavata is disease of locomotor system. Musculoskeletal& joints related complaint accounts for more than 315 million out of patients. Visit per year in India. Joint pain is one of the common disease which is the complaints are big challenges of 21st century. The reason behind this disease is faulty dietary habits, lack of physical activities, faulty sitting, sleeping position, obesity etc. In Ayurvedic literature, ‘Amavata’ is described as separate disease in Madhavnidan. Also it’s easy and simple way fight back and prevent RA and through its preventive and promotivecare. In India the general public is interested in traditional therapies for “Amavata”. Therefore I selected Total 25 patients of Amavata from OPD & IPD unit of Dr. M.N. Agashe Hospital, Satara for my Research project. For Research project I taken drug –“Rasonadighanavati” which is described in Bhaishajya Ratnavali in Amavata Rogadhikar Adhyaya. With my sincere efforts I evaluate the efficacy of Rasonadighanavati in Amavata. Which I described in this Research article.